STRATEGI EKSTRAKURIKULER MUHADHARAH DALAM MENGEMBANGKAN KETERAMPILAN BERBICARA PESERTA DIDIK KELAS TINGGI MADRASAH IBTIDAIYAH RUMAH PENDIDIKAN ISLAM - Yuni Maulani Rahmah; Sundawati Tisnasari; Istinganatul Ngulwiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation strategies of Muhadharah extracurricular activities in developing speaking skills among upper-grade students at Madrasah Ibtidaiyah Rumah Pendidikan Islam, South Jakarta. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation involving the head of the madrasah, extracurricular supervisors, teachers, and students. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that the routine and structured implementation of Muhadharah effectively improves students’ speaking skills, particularly in articulation, intonation, fluency, vocabulary mastery, confidence, and speaking ethics. Supporting factors include the supervisors’ expertise and continuous evaluation, while inhibiting factors involve limited parental support, low student motivation, and time constraints. The study concludes that Muhadharah extracurricular activities serve as an effective medium for enhancing elementary school students’ speaking skills. Keywords: Muhadharah extracurricular activity, speaking skills, elementary school, qualitative study